Optimal detection of random phase signal with Doppler frequency offset in Chirp-BOK multi-antenna system - Hongbing QIU; Xinyu QIAO; Lin ZHENG; Chao YANG; Weiwei YAO; Jing ZHANG (Tongxin xuebao)
When there are Doppler frequency deviation and phase noise in channel,the MIMO-OFDM system with coherent detection requires complicated and accurate frequency offset estimation and Doppler compensation.Based on this,an optimal random phase detection was proposed in multi-antenna Chirp-BOK system,which improved the system capacity by space division multiplexing in the condition of anti-interference and anti-frequency deviation.The equivalent MIMO channel coefficient matrix of multi-antenna Chirp-BOK system was derived as a real matrix,so as to reduce the complexity of channel estimation and avoid to be affected by random phase.A two plus two wireless transceiver system was built on the NI USRP-2942R platform.Simulation and experiment results show that the MIMO-Chirp-BOK system inherits the advantages of low complexity,insensitivity to phase shift and frequency offset of Chirp-BOK communication system.It achieves multiplied communication capacity by increasing the number of antennas.